Histories of Environmental Coalition Building in British Columbia: Using History to Build Working-Class Environmentalism - Harter, John-Henry (Labour / Le Travail, 2022)
On 3 February 1989, leaders of the British Columbia labour movement, members of the environmental movement, and representatives from the Nuu-chah-nulth-aht Tribal Council (ntc) gathered to meet at Tin Wis, the ntc meeting space, in Tofino, BC, to discuss an alliance around environmental issues on the West Coast of Vancouver Island. This article takes this meeting, and subsequent alliance, as a way to explore the impact, potential, and contested meanings of alliances forged among workers, environmentalists, and First Nations in British Columbia in the late 20th century and beyond. In this way, the article examines from a historical perspective what sociologists have framed as the period of new social movements.